Corruption mocking at justice : a theological and ethical perspective on public life in Tanzania and its implications for the Anglican Church of Tanzania - Sebahene, Alfred (Cumbria, Langham Monographs, 2017)
The church has a duty to fight corruption and injustice. The increased awareness globally of corruption and the threat it poses to humanity has led many in the secular and Christian world to seek solutions to stamp out this scourge. Recognizing the crisis caused by corruption in Tanzania, his own country, Dr Alfred Sebahene seeks to understand this social epidemic through the application of theological ethics. As a result of the study the author identifies theological-ethical guidelines that inform and add substance to the church's duty in the public sphere, particularly in the fight against corruption and injustice.
Keywords: Christian ethics; Christian ethics.-- Tanzania; Corruption; Corruption.-- Tanzania; Christian Church Growth.-- Tanzania